RESEARCH INTEGRATED TEACHING IN LANGUAGE CLASSES - Mussabekova, Saule (PEOPLE: International Journal of Social Sciences, 2017)
At Nazarbayev University, which aims to become the first research and world-class university in Kazakhstan, it is important to use research to enhance the student learning experience. In this article, we would like to describe the role of research integrated teaching in Kazakh language classes, where both teacher and students interact with each other and use their research skills to review research papers, collect and analyze data and generate and share enthusiasm in the learning process. This article proposes that research integrated teaching in Kazakh language classes are effective. A high level of interaction between the students and me is promoted by bringing a survey into the classroom. Another method of integrating research and teaching is that students publish the results of their studies. The students indicated in their feedback that this interaction is welcomed and appreciated greatly. Balancing the time spent on teaching and research can lead to more realistic expectations of staff performance. Other factors such as career development can significantly affect teaching productivity and effectiveness. From our experience at Nazarbayev University, therefore, we find that it is possible to integrate research into teaching in language classes.